290 Estimation of variance components due to direct and maternal effects for feed intake for Gelbvieh cattle. (7th December 2018) - Culbertson, M; Enns, R; Speidel, S
Abstract: Through the environment provided by the dam, maternal effects are known to influence performance of progeny for some traits, such as weaning weight. The influence of a maternal genetic effect on feed intake of cattle evaluated after weaning is largely unknown. Since maternal effects can be an important source of variation, the significance of its inclusion for the estimation of variance components for feed intake should be explored. Therefore, the objective of this study was to estimate variance components for direct and maternal effects on feed intake in postweaning cattle. We hypothesized that there would be little maternal effect on feed intake for postweaning cattle. Dry matter feed intake (DMFI) records and pedigree information was provided by the American Gelbvieh Association. Animals with a test start date age (AGE) less than 200 d and greater than 365 d were removed from the analysis to limit the data to postweaning cattle less than a year of age at start of test. The final data set consisted of 3, 920 animals with DMFI records. From these records, a 3-generation pedigree with 17, 971 animals was formed and genetic parameters for feed intake were estimated using ASREML 3.0. The single trait linear animal mixed model contained the fixed effects of contemporary group (sex, pen, test and test year combined) and AGE as a linear covariate; the random additive genetic effects of animal and dam were also included in the model. Estimates of direct additive genetic variance for DMFI was 0.51 ± 0.07 kg 2 /day 2 which corresponded to a heritability 0.42 ± 0.05. The estimate of maternal genetic variance was found to be 0.17 x 10 –7 ± 0.13 x 10 –8 kg 2 /day 2 . These results would indicate that maternal additive genetic effects have no effect on postweaning feed intake phenotypes for Gelbvieh cattle.